Regressive safety practices in the globalised shipping industry. (1st July 2014) - ,
Abstract : The highly fragmented structure of the globalised shipping industry necessitates a regulatory-driven environment for its basic administration. This is a highly safety-critical industry, but regulatory updates only take place after an accident has taken place, based on a retrospective analysis of incidents and accident investigations. This leads to the goal of avoiding the recurrence of past incidents (and arguably newer occurrences too) through regulatory updates of the instruments of the International Maritime Organisation (IMO). This paper highlights the limitations of such an approach and shows how existing health and safety practices in the shipping industry are inadequate to cope with work environments that are changing rapidly as a result of economic and technological pressures. Paradoxically, while safety requires attention to how workers negotiate risks and uncertainties in everyday practice, in the contemporary shipping industry workers are increasingly denied the opportunities for socialisation, rest and organisational support that make such negotiation possible. As a consequence, interpretations of accidents by ''experts'' as matters of human error by the crew acquire the status of fact, further compounding the disempowered position of workers. This leads to a general downward spiral in safety practices. The paper draws on an exhaustive review of the relevant literature as well as empirical evidence obtained from interviews. It critiques the current operational definition of safety in the industry and concludes that the progress the shipping industry believes it is making, mainly, at present, through technology integration, is tardy and may even be regressive and counterproductive.